Human immunodeficiency virus associated spondyloarthropathy: pathogenic insights based on imaging findings and response to highly active antiretroviral treatment. Issue 7 (1st July 2001) - McGonagle, D; Reade, S; Marzo-Ortega, H; Gibbon, W; O'Connor, P; Morgan, A; Melsom, R; Morgan, E; Emery, P
Abstract : The pathogenesis of human immunodeficiency virus (HIV) associated spondyloarthropathy (SpA) is poorly understood. In this case report a patient is described with severe HIV associated reactive arthritis, who on magnetic resonance imaging and sonographic imaging of inflamed knees had extensive polyenthesitis and adjacent osteitis. The arthritis deteriorated despite conventional antirheumatic treatment, but improved dramatically after highly active antiretroviral treatment, which was accompanied by a significant rise in CD4 T lymphocyte counts. The implications of the localisation of pathology and effect of treatment for pathogenic models of SpA and rheumatoid arthritis in the setting of HIV infection are discussed.